Results of the SSM-SICOPS melt tests of the EU-SAFEST project - Gert Langrock; Torsten Keim; Manfred Fischer; Matthias Braun; Sebastian Kohn; Roland Hofmann; Rainer Bezold; Martin Neumeister; Sevostian Bechta; Patrick Isaksson (Annals of Nuclear Energy, 2025)

Linking physical processes to biological responses: Interdisciplinary observational insights into the enhanced biological productivity of the Cape Verde Archipelago - Florian Schütte; Anna Christina Hans; Marco Schulz; Rebecca Hummels; Olivier Assokpa; Peter Brandt; Rainer Kiko; Arne Körtzinger; Björn Fiedler; Tim Fischer; Elizandro Rodrigues; Henk-Jan Hoving; et al. (Progress in Oceanography, 2025)

Taken to extremes: Loss of plastid rpl32 in Streptophyta and Cuscuta’s unconventional solution for its replacement - Karsten Fischer; Sondre Valentin Jordbræk; Stian Olsen; Mathias Bockwoldt; Rainer Schwacke; Björn Usadel; Kirsten Krause (Molecular Phylogenetics and Evolution, 2025)

Evolution of chemically induced cracks in alkali feldspar: thermodynamic analysis - Rainer Abart; Elena Petrishcheva; Gerlinde Habler; Christoph Sutter; Franz Dieter Fischer; Jozef Predan; Marko Kegl; Franz G. Rammerstorfer (Physics and Chemistry of Minerals, 2022)
A system of edge cracks was applied to polished (010) surfaces of K-rich gem-quality alkali feldspar by diffusion-mediated cation exchange between oriented feldspar plates and a Na-rich NaCl–KCl salt melt. The cation exchange produced a Na-rich layer at and beneath the specimen surface, and the associated strongly anisotropic lattice contraction lead to a tensile stress state at the specimen surface, which induced fracturing. Cation exchange along the newly formed crack flanks produced Na-enriched diffusion halos around the cracks, and the associated lattice contraction and tensile stress state caused continuous crack growth. The cracks nucleated with non-uniform spacing on the sample surface and quickly attained nearly uniform spacing below the surface by systematic turning along their early propagation paths. In places, conspicuous wavy cracks oscillating several times before attaining their final position between the neighboring cracks were produced. It is shown that the evolution of irregularly spaced towards regularly spaced cracks including the systematic turning and wavyness along the early propagation paths maximizes the rate of free energy dissipation in every evolutionary stage of the system. Maximization of the dissipation rate is suggested as a criterion for selection of the most probable evolution path for a system undergoing chemically induced diffusion mediated fracturing in an anisotropic homogeneous brittle material.

The 10th International Conference on Life Cycle Management 2021—Stuttgart, Germany, September 05–08, 2021 - Matthias Fischer; Mercedes Barkmeyer; Stefan Albrecht; Anna Braune; Philip Leistner; Rainer Seifert; Johannes Kreissig (The International Journal of Life Cycle Assessment, 2021)

Semi-rational design of cellobiose dehydrogenase for increased stability in the presence of peroxide - Ana Marija Balaž; Jelena Stevanović; Raluca Ostafe; Marija Blazić; Karla Ilić Đurđić; Rainer Fischer; Radivoje Prodanović (Molecular Diversity, 2020)

Gene expression variability between randomly and targeted transgene integration events in tobacco suspension cell lines - Janina Kirchhoff; Andreas Schiermeyer; Katja Schneider; Rainer Fischer; W. Michael Ainley; Steven R. Webb; Helga Schinkel; Stefan Schillberg (Plant Biotechnology Reports, 2020)
Genome editing tools such as zinc-finger nucleases provide novel strategies for genetic manipulation in plants. Unlike agrobacterium-mediated or direct gene transfer, which introduce genes randomly into the genome and thereby potentially resulting in high variation of gene expression, the targeted gene addition provides predictable integration of DNA sequences into a specified location of the plant genome. We investigated whether various independent cell lines that all contain a transgene placed in the same genomic locus by zinc-finger nuclease-mediated homologous recombination (HR) would yield a more reproducible and homogeneous level of expression compared to integration events generated via agrobacterium-mediated transformation at random sites. The variance of gene expression of targeted HR events and random integration events was analyzed in Nicotiana tabacum L cv. Bright Yellow 2 (BY-2) suspension cells by measuring protein amount produced from the transgene by flow cytometry, thus providing the first report on positional effects of marker gene expression in a quickly proliferating plant suspension cell line. Marker protein levels of targeted HR and single-copy random events covered a similar range; however, the uniformity of protein expression in a given cell line was significantly higher in targeted events than in lines with randomly inserted transgene; the same is true for the overall viability of protoplasts from HR lines. In conclusion, using targeted insertion into a qualified locus of a well-characterized line leads to more reliable results than random insertion into the genome.

Systemic LPS induces toll-like receptor 3 (TLR3) expression and apoptosis in testicular mouse tissue - Lene N. Nejsum; Adrian Piec; Monika Fijak; Christina V. Ernstsen; Dania Fischer; Thorsten J. Maier; Ralf Kinscherf; Rainer Hofmann; Anja Urbschat (Cell and Tissue Research, 2019)

Detection and Specific Elimination of EGFR+ Ovarian Cancer Cells Using a Near Infrared Photoimmunotheranostic Approach - Dirk Bauerschlag; Ivo Meinhold-Heerlein; Nicolai Maass; Andreas Bleilevens; Karen Bräutigam; Wa’el Al Rawashdeh; Stefano Di Fiore; Anke Maria Haugg; Felix Gremse; Julia Steitz; Rainer Fischer; Elmar Stickeler; et al. (Pharmaceutical Research, 2017)

Statistical experimental designs for the production of secondary metabolites in plant cell suspension cultures - Christian Schmitz; Leonie Fritsch; Rainer Fischer; Stefan Schillberg; Stefan Rasche (Biotechnology Letters, 2016)

Utilizing Regulatory Networks for Pluripotency Assessment in Stem Cells - Björn Brändl; Bernhard M. Schuldt; Lena Böhnke; Oliver Keminer; Lea A. I. Vaas; Rainer Fischer; Franz-Josef Müller; Ole Pless (Current Stem Cell Reports, 2016)

Thanatin confers partial resistance against aflatoxigenic fungi in maize (Zea mays) - Max Schubert; Marcel Houdelet; Karl-Heinz Kogel; Rainer Fischer; Stefan Schillberg; Greta Nölke (Transgenic Research, 2015)

Next-generation sequencing is a robust strategy for the high-throughput detection of zygosity in transgenic maize - Leonie Fritsch; Rainer Fischer; Christoph Wambach; Max Dudek; Stefan Schillberg; Florian Schröper (Transgenic Research, 2015)

Yeast surface display is a novel tool for the rapid immunological characterization of plant-derived food allergens - Milica Popovic; Radivoje Prodanovic; Raluca Ostafe; Stefan Schillberg; Rainer Fischer; Marija Gavrovic-Jankulovic (Immunologic Research, 2015)

Image-based analysis of cell-specific productivity for plant cell suspension cultures - Heide Havenith; Nicole Raven; Stefano Di Fiore; Rainer Fischer; Stefan Schillberg (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Innovative Produktion pharmazeutischer Proteine in Pflanzen - Johannes Felix Buyel; Andreas Reimann; Jürgen Drossard; Rainer Fischer (BIOspektrum, 2014)

Comparison of plant-based expression platforms for the heterologous production of geraniol - Nikolay Vasilev; Christian Schmitz; Lemeng Dong; Anneli Ritala; Nicole Imseng; Suvi T. Häkkinen; Sander van der Krol; Regine Eibl; Kirsi-Marja Oksman-Caldentey; Harro Bouwmeester; Rainer Fischer; Stefan Schillberg (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

The impact of HLA-C matching depends on the C1/C2 KIR ligand status in unrelated hematopoietic stem cell transplantation - Johannes C. Fischer; Guido Kobbe; Jürgen Enczmann; Rainer Haas; Markus Uhrberg (Immunogenetics, 2012)

In vivo expression and binding activity of scFv-RWAV, which recognizes the coat protein of tomato leaf curl New Delhi virus (family Geminiviridae) - Adel M. Zakri; Angelika Ziegler; Ulrich Commandeur; Rainer Fischer; Lesley Torrance (Archives of Virology, 2012)

Biochemical properties of the matrix metalloproteinase NtMMP1 from Nicotiana tabacum cv. BY-2 suspension cells - Manoj K. Mandal; Rainer Fischer; Stefan Schillberg; Andreas Schiermeyer (Planta, 2010)

Viral membrane proteins - Wolfgang B. Fischer; Gerhard Thiel; Rainer H. A. Fink (European Biophysics Journal, 2010)

Modulating the activity of the channel-forming segment of Vpr protein from HIV-1 - Chin-Pei Chen; Clemens Kremer; Peter Henklein; Ulrich Schubert; Rainer H. A. Fink; Wolfgang B. Fischer (European Biophysics Journal, 2010)

Generation and characterization of a scFv against recombinant coat protein of the geminivirus tomato leaf curl New Delhi virus - Adel M. Zakri; Angelika Ziegler; Lesley Torrance; Rainer Fischer; Ulrich Commandeur (Archives of Virology, 2010)

The Promoters of Forisome Genes MtSEO2 and MtSEO3 Direct Gene Expression to Immature Sieve Elements in Medicago truncatula and Nicotiana tabacum - Gundula A. Noll; Boris Rüping; Antonia M. Ernst; Maria Bucsenez; Richard M. Twyman; Rainer Fischer; Dirk Prüfer (Plant Molecular Biology Reporter, 2009)

Distributions and characteristics of dissolved organic matter in temperate coastal waters (Southern North Sea) - Andrea Lübben; Olaf Dellwig; Sandra Koch; Melanie Beck; Thomas H. Badewien; Sibylle Fischer; Rainer Reuter (Ocean Dynamics, 2009)

Recombinant-antibody-mediated resistance against Tomato yellow leaf curl virus in Nicotiana benthamiana - Mohammad Reza Safarnejad; Rainer Fischer; Ulrich Commandeur (Archives of Virology, 2009)

An assay for the detection of grapevine leafroll-associated virus 3 using a single-chain fragment variable antibody - Laura Cogotzi; Annalisa Giampetruzzi; Greta Nölke; Martin Orecchia; Vito Elicio; Maria Antonietta Castellano; Giovanni P. Martelli; Rainer Fischer; Stefan Schillberg; Pasquale Saldarelli (Archives of Virology, 2009)

Generation and characterization of a recombinant antibody fragment that binds to the coat protein of grapevine leafroll-associated virus 3 - Martin Orecchia; Greta Nölke; Pasquale Saldarelli; Mariangela Dell’Orco; Kerstin Uhde-Holzem; Markus Sack; Giovanni Martelli; Rainer Fischer; Stefan Schillberg (Archives of Virology, 2008)

MEFASPACE: A Model Predicting Freight Transport from Materials Flows, and Transport Activity in Europe - Marina Fischer-Kowalski; Veronika Gaube; Gerhard Rainer (Journal of Industrial Ecology, 2008)

Spatial and temporal regulation of the forisome gene for1 in the phloem during plant development - Gundula A. Noll; Maria E. Fontanellaz; Boris Rüping; Ahmed Ashoub; Aart J. E. van Bel; Rainer Fischer; Michael Knoblauch; Dirk Prüfer (Plant Molecular Biology, 2007)

Comparative survey of plastid and mitochondrial targeting properties of transcription factors in Arabidopsis and rice - Rainer Schwacke; Karsten Fischer; Bernd Ketelsen; Karin Krupinska; Kirsten Krause (Molecular Genetics and Genomics, 2007)

Analysis of Genetic Variation Among Accessions of Pueraria montana (Lour.) Merr. var. lobata and Pueraria phaseoloides (Roxb.) Benth. based on RAPD Markers - Bettina Heider; Elke Fischer; Tanja Berndl; Rainer Schultze-Kraft (Genetic Resources and Crop Evolution, 2007)

In planta AKT2 subunits constitute a pH- and Ca2+-sensitive inward rectifying K+ channel - Andreas Latz; Natalya Ivashikina; Susanne Fischer; Peter Ache; Toshio Sano; Dirk Becker; Rosalia Deeken; Rainer Hedrich (Planta, 2007)

Constitutive knox1 gene expression in dandelion (Taraxacum officinale, Web.) changes leaf morphology from simple to compound - Kai J. Müller; Xinqiang He; Rainer Fischer; Dirk Prüfer (Planta, 2006)

Endosperm-Specific Co-Expression of Recombinant Soybean Ferritin and Aspergillus Phytase in Maize Results in Significant Increases in the Levels of Bioavailable Iron - Georgia Drakakaki; Sylvain Marcel; Raymond P. Glahn; Elizabeth K. Lund; Sandra Pariagh; Rainer Fischer; Paul Christou; Eva Stoger (Plant Molecular Biology, 2005)

Production of an active recombinant thrombomodulin derivative in transgenic tobacco plants and suspension cells - Helga Schinkel; Andreas Schiermeyer; Raphael Soeur; Rainer Fischer; Stefan Schillberg (Transgenic Research, 2005)

Chemolabile cellular microarrays for screening small molecules and peptides - Antje Hoff; Thomas André; Rainer Fischer; Söhnke Voss; Michael Hulko; Udo Marquardt; Karl-Heinz Wiesmüller; Roland Brock (Molecular Diversity, 2004)

Transient gene expression of recombinant terpenoid indole alkaloid enzymes inCatharanthus roseus leaves - Stefano Di Fiore; Verena Hoppmann; Rainer Fischer; Stefan Schillberg (Plant Molecular Biology Reporter, 2004)

'Molecular farming' of antibodies in plants - Stefan Schillberg; Rainer Fischer; Neil Emans (The Science of Nature, 2003)

Antibody molecular farming in plants and plant cells - Stefan Schillberg; Neil Emans; Rainer Fischer (Phytochemistry Reviews, 2002)

Antibody-Based Resistance to Plant Pathogens - Stefan Schillberg; Sabine Zimmermann; Mei-Yun Zhang; Rainer Fischer (Transgenic Research, 2001)

Molecular farming of pharmaceutical proteins - Rainer Fischer; Neil Emans (Transgenic Research, 2000)

Cereal crops as viable production and storage systems for pharmaceutical scFv antibodies - Eva Stöger; Carmen Vaquero; Esperanza Torres; Markus Sack; Liz Nicholson; Jürgen Drossard; Sarah Williams; Duncan Keen; Yolande Perrin; Paul Christou; Rainer Fischer (Plant Molecular Biology, 2000)

Rice cell culture as an alternative production system for functional diagnostic and therapeutic antibodies - Esperanza Torres; Carmen Vaquero; Liz Nicholson; Markus Sack; Eva Stöger; Jürgen Drossard; Paul Christou; Rainer Fischer; Yolande Perrin (Transgenic Research, 1999)

Apoplastic and cytosolic expression of full‐size antibodies and antibody fragments in Nicotiana tabacum - Stefan Schillberg; Sabine Zimmermann; Andreas Voss; Rainer Fischer (Transgenic Research, 1999)

Agricultural reclamation of disturbed soils in a lignite mining area using municipal and coal wastes: the humus situation at the beginning of reclamation - Nadja Zier; Rainer Schiene; Helmut Koch; Klaus Fischer (Plant and Soil, 1999)

Structure and dynamics of human interphase chromosome territories in vivo - D. Zink; T. Cremer; Rainer Saffrich; Roger Fischer; Michael F. Trendelenburg; Wilhelm Ansorge; Ernst H. K. Stelzer (Human Genetics, 1998)

Citrus meletensis (Rutaceae), a new species from the Pliocene of Valdarno (Italy) - Thilo C. Fischer; Rainer Butzmann (Plant Systematics and Evolution, 1998)